Porous material, composition, heat insulating material, sound absorbing material, interlayer film for laminated glass, and method for producing porous material
Patent Information
- Application Number
- JP2023142827
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-14
AI Technical Summary
【0010】 本開示によれば、力学特性及び透明性に優れる新規な多孔体材料が提供される。また、本開示によれば、当該多孔体材料を含む組成物、断熱材料、吸音材料及び合わせガラス中間膜が提供される。また、本開示によれば、当該多孔体材料の製造方法が提供される。
Smart Images

Figure 2025035645000002 
Figure 2025035645000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a porous material, a composition, a thermal insulation material, a sound absorbing material, a laminated glass interlayer film, and a method for producing the porous material. [Background technology]
[0002] The majority of heat loss in homes (60-70%) occurs through openings such as windows. To realize a sustainable society, it is necessary to reduce the environmental impact by suppressing heat loss from openings. One method for preventing heat loss while maintaining the necessary function of windows, which is to allow in natural light, is to use transparent insulation materials. Aerogel is a typical example of a transparent insulation material.
[0003] Aerogel is a porous structure with a fine skeleton and low density. Therefore, aerogel has a large specific surface area, high thermal insulation and high transparency. The most common aerogel is silica aerogel, which has a skeleton of silica (silicon dioxide).
[0004] However, silica aerogel is so fragile that it breaks even with minute deformations, and this poor mechanical property is one of the factors preventing the practical use of silica aerogel.
[0005] Aerogel materials other than silica include polysaccharides including cellulose and chitin. For example, Non-Patent Document 1 below reports an aerogel made from chitin. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Jintian, Wang. Preparation of a novel double crosslinked chitin aerogel via etherification with high strength, Carbohydrate Polymers, 2021, Vol.265, article. 118014. Summary of the Invention [Problem to be solved by the invention]
[0007] Aerogels made from chitin-based compounds have high toughness, but they lack transparency and there is room for improvement in terms of transparency.
[0008] The present disclosure provides a novel porous material having excellent mechanical properties and transparency. The present disclosure also provides a composition, a heat insulating material, a sound absorbing material, and an interlayer film for laminated glass, each containing the porous material. The present disclosure also provides a method for producing the porous material. [Means for solving the problem]
[0009] In order to solve the above problems, the present disclosure provides the following porous material, composition, heat insulating material, sound absorbing material, and method for producing a porous material. [1] A porous material that is a colorless and transparent aerogel containing chitin-based compounds. [2] The porous material according to [1], wherein the content of the chitin-based compound is 10 mass% or more based on the total amount of the porous material. [3] The porous material according to [1] or [2], which has a haze value per mm thickness at a wavelength of 600 nm of 20% or less. [4] The porous material according to any one of [1] to [3], which has a total light transmittance per mm thickness at a wavelength of 600 nm of 80% or more. [5] The porous material according to any one of [1] to [4], wherein the chitin-based compound has a degree of N-acetylation of 80% or more. [6] A composition comprising the porous material according to any one of [1] to [5]. [7] The composition described in [6], which is in the form of a plate. [8] A heat insulating material comprising the porous material according to any one of [1] to [5]. [9] A sound-absorbing material comprising the porous material according to any one of [1] to [5].
[10] A laminated glass interlayer film comprising the porous material according to any one of [1] to [5].
[11] A method for producing a porous material according to any one of [1] to [5], comprising the steps of: (A) preparing a wet gel containing the chitin-based compound; (B) drying the wet gel to obtain a porous material; A method for producing a porous material comprising the steps of: Effect of the Invention
[0010] The present disclosure provides a novel porous material having excellent mechanical properties and transparency. The present disclosure also provides a composition, a heat insulating material, a sound absorbing material, and a laminated glass interlayer film that contain the porous material. The present disclosure also provides a method for producing the porous material. [Brief description of the drawings]
[0011] [Figure 1] Fig. 1(a) is a graph showing the measurement results of the total light transmittance of Example 4. Fig. 1(b) is a graph showing the measurement results of the haze value of Example 4. Fig. 1(c) is a graph showing the measurement results of the pore size of the aerogel of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present disclosure will be described in detail. The present disclosure is not limited to the embodiments described below. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range may be replaced with the upper limit or lower limit of another numerical range. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with the value shown in the examples.
[0013] [Porous materials] The porous material according to the present embodiment is a colorless and transparent aerogel containing a chitin-based compound.
[0014] (Aerogel) Hereinafter, the aerogel according to this embodiment (hereinafter, simply referred to as "aerogel") will be described. In this specification, "aerogel" means a dry gel obtained by drying a wet gel by a supercritical drying method. The aerogel has a mesh-like fine structure. The aerogel has a cluster structure in which fibers of a chitin-based compound are bonded. Between the skeletons formed by these clusters, there are pores of less than 100 nm. As a result, the aerogel has a three-dimensional fine porous structure.
[0015] Aerogel is colorless. In this specification, "colorless" means that in a graph obtained by measuring the total light transmittance of a porous material per mm thickness, the vertical axis represents the total light transmittance and the horizontal axis represents the wavelength, the graph does not have a local absorption peak in the visible light region (400 to 800 nm).
[0016] The total light transmittance refers to a value obtained by measuring the amount of incident light and the amount of total transmitted light, and calculating the total light transmittance = (total amount of transmitted light) / (amount of incident light) x 100. The amount of incident light and the total amount of transmitted light refer to values measured by ultraviolet-visible-near infrared spectroscopy.
[0017] Aerogel is transparent. In this specification, "transparent" means that the maximum haze value of the porous material per 1 mm thickness in the visible light region (400 to 800 nm) is 30% or less. The haze value is measured using ultraviolet-visible-near infrared spectroscopy.
[0018] The aerogel may have a haze value of 20% or less per mm thickness at a wavelength of 600 nm, the haze value being measured under conditions of a temperature of 23° C. and a relative humidity of 50%.
[0019] The total light transmittance of the aerogel per mm thickness at a wavelength of 600 nm may be 80% or more, or 90% or more, as measured under conditions of a temperature of 23° C. and a relative humidity of 50%.
[0020] From the viewpoint of ensuring the mechanical strength of the aerogel, the average pore size of the aerogel is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. The pore size is measured by analyzing the adsorption side of the nitrogen adsorption isotherm using a specific surface area / pore size distribution measuring device using the BJH method.
[0021] The standard deviation of the pore diameter of the aerogel is preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less, since the transparency and strength of the aerogel are further improved.
[0022] The bulk density of aerogel at a temperature of 23°C and a relative humidity of 50% is 50mg / cm because the mechanical strength is higher. 3 It is preferable that the concentration is 100 mg / cm or more. 3 More preferably, it is 150 mg / cm or more. 3 The bulk density of the aerogel is preferably 300 mg / cm or more. 3 The bulk density is measured by a bulk density measuring device.
[0023] The porosity of the aerogel at a temperature of 23° C. and a relative humidity of 50% may be 80 to 99%. The porosity is a value calculated by measuring the bulk density and the true density, and then calculating the porosity as follows: porosity=(1-(bulk density) / (true density))×100.
[0024] The specific surface area of aerogel is 300m 2 / g or more, 400m 2 / g or more, or 500m 2 The specific surface area of the aerogel can be calculated by measuring it using a BET specific surface area measurement method.
[0025] The thermal conductivity of the aerogel may be, for example, 50 mW / (m·K) or less, 40 mW / (m·K) or less, or 30 mW / (m·K) or less. The thermal conductivity of the aerogel is measured using a thermal diffusivity measuring device or a thermal conductivity measuring device at a temperature of 23° C. and a relative humidity of 50%.
[0026] The compressive modulus of the aerogel may be, for example, 0.5 MPa or more, 1.0 MPa or more, or 2.0 MPa or more. The compressive modulus refers to a value measured as the slope of the elastic region of a stress-strain curve calculated by a compression test using a mechanical testing machine at a temperature of 23° C. and a relative humidity of 50%.
[0027] The energy absorption per unit volume of aerogel at 70% strain is 100 kJ / m 3 More than 200kJ / m 3 More than 300kJ / m 3 More than 400kJ / m 3 More than 500kJ / m 3 More than 600kJ / m 3 or more than 700kJ / m 3 The energy absorption amount means a value measured as an area of a 0 to 70% strain region of a calculated stress-strain curve in a compression test using a mechanical testing machine at a temperature of 23°C and a relative humidity of 50%.
[0028] The aerogel contains a chitin-based compound. Examples of chitin-based compounds include chitin and chitosan. The chitin-based compounds may be used alone or in combination of two or more. In this specification, "chitin" refers to β-1,4-poly-D-glucosamine in which 60% or more of the amino groups are acetylated. In this specification, "chitosan" refers to β-1,4-poly-D-glucosamine in which less than 60% of the amino groups are acetylated.
[0029] Commercially available chitin-based compounds include, for example, "Chitosan 10" and "Chitosan 100" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0030] The degree of N-acetylation in the chitin-based compound is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more. When the degree of N-acetylation is in the above-mentioned range, the aerogel is colorless and has better transparency. The degree of N-acetylation in the chitin-based compound may be 70% or less.
[0031] The proportion of chitin in the chitin-based compound is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. When the proportion of chitin in the chitin-based compound is in the above numerical range, the aerogel is colorless and has even better transparency. The proportion of chitin in the chitin-based compound may be 20% by mass or less.
[0032] The proportion of chitosan in the chitin-based compound may be from 1% by mass to 10% by mass.
[0033] The content of the chitin-based compound in the aerogel may be 10% by mass or more, and from the viewpoint of transparency and strength, it is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more, based on the total amount of the aerogel. The content of the chitin-based compound in the aerogel may be 100% by mass.
[0034] The weight average molecular weight of the chitin-based compound is not particularly limited, but is, for example, 1000 to 1500000. In this specification, the weight average molecular weight means a weight average molecular weight determined by GPC method in terms of standard polystyrene.
[0035] The aerogel may contain components other than chitin-based compounds, such as cellulose-based compounds and layered inorganic additives.
[0036] The aerogel can be suitably used for applications such as packing materials, wrapping materials, aerospace materials, home appliance materials, industrial equipment materials, automotive materials, and building materials.
[0037] Although the aerogel according to the present embodiment has been described above, the porous material of the present disclosure is not limited to the above embodiment. The porous material may be, for example, a xerogel obtained by drying a wet gel by evaporation drying. The porous material may be, for example, a cryogel obtained by drying a wet gel by freeze drying.
[0038] [Method of manufacturing porous materials] The method for producing a porous material according to this embodiment will be described below. The method for producing a porous material includes the following steps. (A) A step of preparing a wet gel containing a chitin-based compound (C) A step of replacing the solvent in the wet gel (B) Drying the wet gel
[0039] (Process (A)) Step (A) is a step of preparing a wet gel containing a chitin-based compound. The wet gel is obtained using a solution containing a chitin-based compound. The solution containing a chitin-based compound may be obtained by dissolving a chitin-based compound in a solvent. Examples of the solvent include water, acetic acid, and methanol.
[0040] The solution containing the chitin-based compound may be gelled, for example, by adding a gelling agent in a cooled state, placing the solution in a container, and leaving it at room temperature. This results in a wet gel. By cooling the solution, adding a gelling agent, and leaving it at room temperature, the distance between the fibers of the chitin-based compound becomes uniform. This results in a porous material having a small average pore size and a small standard deviation. As a result, the porous material has high transparency and high strength.
[0041] The gelling agent may be, for example, acetic anhydride, and the amount of the gelling agent may be 80 to 1000 parts by mass with respect to 100 parts by mass of the chitin compound.
[0042] The cooling temperature may be, for example, -15 to -10°C. The temperature at which the solution is left after being cooled may be, for example, 10 to 30°C.
[0043] (Process (C)) Step (C) is a step of replacing the solvent in the wet gel. Examples of the solvent that can be used for such replacement include alcohols such as methanol, ethanol, and isopropanol, aromatic compounds such as benzene and toluene, hydrocarbon solvents such as hexane, amide solvents, ketone solvents, and ester solvents.
[0044] The method for producing a porous material according to this embodiment includes step (C), but the method for producing a porous material according to the present disclosure does not necessarily include step (C).
[0045] (Process (B)) Step (B) is a step of drying the wet gel after the solvent replacement in step (C), thereby obtaining a porous material.
[0046] When the porous material is an aerogel, the wet gel is dried by a supercritical drying method. The conditions for drying by the supercritical drying method are not particularly limited, and a known drying method can be adopted. For example, a known drying method using supercritical carbon dioxide can be adopted.
[0047] Drying of the wet gel may be by methods other than supercritical drying, such as, for example, evaporative drying and freeze drying.
[0048] When the porous material is a xerogel, the wet gel is dried at a temperature below the critical point of the solvent contained in the wet gel. When the solvent is replaced in step (B), the wet gel is dried at a temperature below the critical point of the solvent used for the replacement. The drying temperature may be, for example, 10 to 70° C. The drying pressure may be, for example, atmospheric pressure.
[0049] [Composition] The composition according to the present embodiment will be described below. The composition contains the porous material according to the above embodiment. The composition according to the present embodiment may further contain a binder. Examples of the binder include a resin.
[0050] Examples of the resin include polyester, epoxy resin, bismaleimide resin, phenol resin, melamine resin, and silicon resin.
[0051] The shape of the composition may be, for example, a plate, pellet, cylinder, cone, polygonal prism, polygonal pyramid, or sphere.
[0052] [Molded body] The molded body according to this embodiment will be described below. The molded body is formed by molding the composition according to the above embodiment. When the composition contains a resin, the molded body may be molded by curing the resin. Since the molded body has excellent mechanical properties, it can be suitably used for the same applications as the porous body material according to the above embodiment.
[0053] [Structural material] The structural material according to this embodiment will be described below. The structural material is composed of a combination of a plurality of the porous body materials according to the above embodiment. The structural material may be, for example, a plurality of porous body materials whose surfaces are bonded together with an adhesive or the like. The structural material can be used for the same purposes as the porous body material according to the above embodiment.
[0054] [Insulation material] The heat insulating material according to this embodiment will be described below. The heat insulating material includes the porous material according to the above embodiment. Therefore, the heat insulating material is excellent in transparency, heat insulation, and mechanical properties. The heat insulating material can be used for the same applications as the porous material according to the above embodiment. Since the heat insulating material is excellent in transparency and heat insulation, it can be particularly suitably used as a heat insulating material for openings such as windows of houses.
[0055] [Sound absorbing material] The sound-absorbing material according to this embodiment will be described below. The sound-absorbing material includes the porous material according to the above embodiment. The sound-absorbing material has excellent sound absorbing properties because the porous material has a porous structure. The sound-absorbing material can be used for the same applications as the porous material according to the above embodiment.
[0056] [Laminated glass interlayer film] Hereinafter, the laminated glass interlayer film according to this embodiment will be described. The laminated glass interlayer film contains the porous material according to the above embodiment. The laminated glass interlayer film is used in laminated glass including the laminated glass interlayer film and glass plates located on both sides of the laminated glass interlayer film. Such laminated glass has excellent transparency, heat insulation, and mechanical properties. EXAMPLES
[0057] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.
[0058] [Production of aerogel] Example 1 0.15g of Chitosan 100 (trade name, Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 15mL of aqueous acetic acid solution (1.5mL of acetic acid and 13.5mL of water) to obtain a mixed solution. 60mL of methanol was added to the mixed solution, which was then stirred and cooled to -12°C. 0.9mL of acetic anhydride was added to the mixed solution and stirred. The mixed solution was poured into a container. The mixed solution was allowed to stand at 25°C to allow gelation to proceed, resulting in a transparent wet gel. At this time, the N-acetylation degree of the chitin-based compound was 98.5%.
[0059] The obtained wet gel was washed with methanol to remove acetic acid. After washing, the methanol in the wet gel was replaced with ethanol. The wet gel was then dried using supercritical carbon dioxide. This resulted in a plate-shaped aerogel (length: 3 cm, width: 3 cm, thickness: 1 cm).
[0060] Example 2 An aerogel was obtained in the same manner as in Example 1, except that 0.30 g of Chitosan 100 was used instead of 0.15 g of Chitosan 100.
[0061] Example 3 An aerogel was obtained in the same manner as in Example 1, except that 0.45 g of Chitosan 100 was used instead of 0.15 g of Chitosan 100.
[0062] Example 4 An aerogel was obtained in the same manner as in Example 1, except that 0.75 g of Chitosan 100 was used instead of 0.15 g of Chitosan 100.
[0063] [Measurement of total light transmittance] The total light transmittance of the obtained aerogel was measured. The total light transmittance was calculated by measuring the amount of incident light and the amount of total transmitted light, and the total light transmittance was calculated as total light transmittance = (total transmitted light amount) / (incident light amount) × 100. For the measurement, an ultraviolet-visible-near infrared spectrophotometer V-670 (device name, manufactured by JASCO Corporation) was used. The measurement conditions were a temperature of 23°C and a relative humidity of 50%. The total light transmittance at a wavelength of 600 nm when the thickness of the aerogel was converted to 1 mm is shown in Table 1. The measurement results of Example 4 are shown in FIG. 1 (a). It was also confirmed that the aerogels according to each example did not have a local absorption peak in the visible light region (400 to 800 nm).
[0064] [Haze value measurement] The haze value of the obtained aerogel was measured. For the measurement, an ultraviolet-visible-near infrared spectrophotometer V-670 (apparatus name, manufactured by JASCO Corporation) was used. The measurement conditions were a temperature of 23°C and a relative humidity of 50%. The haze value at a wavelength of 600 nm when the thickness of the aerogel was converted to 1 mm is shown in Table 1. The measurement result of Example 4 is shown in FIG. 1(b). It was also confirmed that the aerogel according to each example had a maximum haze value of 90% or less in the visible light region (400 to 800 nm).
[0065] [Measurement of pore size] The pore diameter of the obtained aerogel was measured. Specifically, the average value and standard deviation of the pore diameters measured using a specific surface area / pore distribution measuring device (Quantachrome Corporation, product name: "NOVA4200e") were calculated. The results are shown in Table 1. For the aerogel of Example 4, a graph showing the differential pore volume on the vertical axis and the pore diameter on the horizontal axis is shown in Figure 1 (c).
[0066] [Measurement of thermal conductivity] The thermal conductivity of the obtained aerogel was measured. Specifically, the thermal conductivity was measured using a thermal diffusivity measuring device (Ai-Phase Corporation, product name: "ai-Phase Mobile 1u"). The measurement conditions were a temperature of 23°C and a relative humidity of 50%. The results are shown in Table 1.
[0067] [Measurement of compressive elastic modulus and energy absorption] The compressive modulus of the obtained aerogel and the energy absorption amount per unit volume at 70% strain of the obtained aerogel were measured. Specifically, the compressive modulus and the energy absorption amount were measured by performing a compression test on the aerogel using a mechanical testing machine (manufactured by Shimadzu Corporation, product name: "EZ-TEST") at a temperature of 23°C and a relative humidity of 50%. The results are shown in Table 1.
[0068] Table 1 shows the bulk density, porosity, specific surface area, thermal conductivity, compressive modulus, and energy absorption of four nanocellulose aerogels disclosed in the literature (Yuri, Kobayashi. Aerogels with 3D Ordered Nanofiber Skeletons of Liquid-Crystalline Nanocellulose Derivatives as Tough and Transparent Insulators, Angewandte Chemie, 2014, Vol. 53, Issue 39, pages 10394-10397.).
[0069] [Table 1]
Claims
1. A porous material that is a colorless and transparent aerogel containing chitin-based compounds.
2. The porous material according to claim 1 , wherein the content of the chitin-based compound is 10 mass % or more based on the total amount of the porous material.
3. 2. The porous material according to claim 1, which has a haze value per mm thickness at a wavelength of 600 nm of 20% or less.
4. 2. The porous material according to claim 1, which has a total light transmittance per mm thickness at a wavelength of 600 nm of 80% or more.
5. 2. The porous material according to claim 1, wherein the chitin-based compound has a degree of N-acetylation of 80% or more.
6. A composition comprising the porous material according to any one of claims 1 to 5.
7. The composition of claim 6 which is in the form of a plate.
8. A heat insulating material comprising the porous material according to any one of claims 1 to 5.
9. A sound absorbing material comprising the porous material according to any one of claims 1 to 5.
10. A laminated glass interlayer comprising the porous material according to any one of claims 1 to 5.
11. A method for producing the porous material according to any one of claims 1 to 5, (A) preparing a wet gel containing the chitin-based compound; (B) drying the wet gel to obtain a porous material; A method for producing a porous material comprising the steps of: